Mapeamento de quinze instrumentos de avaliaç\~ao dos investimentos externos - Michelle Ratton Sanchez; Ana Maria Moras; Carolina Bianchini Bonini; Manu Misra (Instituto de Pesquisa Econômica Aplicada (IPEA), 2022)
– Investment Screening Mechanisms (ISM) are legal rules created to control and assess the entry of direct investments from foreign jurisdictions. This discussion paper is premised on the observation of a marked increase in the institutionalization and implementation of ISM in recent years, regardless of the type of domestic economy. It selects fifteen ISM for a descriptive analysis of their organizational structures and procedures, including: Australia, Canada, China, Germany, India, Japan, South Korea, Mexico, Portugal, Russia, South Africa, Spain, the United Kingdom, the United States, and the European Union. Although the criteria for controlling and evaluating foreign investment contains national security as a shared concern, this paper identifies a significant diversity regarding the profile of the institutions responsible for investment screening, including their scope and their procedures for assessment. As a final remark, the paper raised critical concerns about ISM based on its analysis and the literature.
Keywords: F21; G11; H00; H56; O16; O20; 330; foreign investment; screening mechanisms; national security